VIABILIDADE DO EMPREGO DE NOTAS NA AVALIAÇÃO DE ALGUNS CARACTERES DO FEIJOEIRO (PHASEOLUS VULGARIS L.) - JÚNIOR, OSWALDO GOMES MARQUES; RAMALHO, MAGNO A. PATTO; FERREIRA, DANIEL FURTADO; SANTOS, JOAO BOSCO DOS (Revista Ceres, 2015)
.